Developmental and sequenced one-to-one educational intervention (DS1-EI) for autism spectrum disorder and intellectual disability: a two-year interim report of a randomized single-blind multicenter controlled trial - Antoine Tanet; Annick Hubert-Barthelemy; Marie-Noëlle Clément; François Soumille; Graciela C. Crespin; Hugues Pellerin; François-André Allaert; David Cohen; Catherine Saint-Georges; the GPIS study group (BMC, 2020)
Abstract Background Children with autism spectrum disorder (ASD) and moderate to severe intellectual disability (ID) face many challenges. There is little evidence-based research into educational settings for children with ID and ASD and in France. Little is known about how this unserved population could benefit from intervention and education. This study assessed the feasibility and efficacy of a new intervention model using an individualized educational approach. Methods We conducted a randomized, single-blind controlled trial to assess a novel intervention: the "Developmental and Sequenced One-to-One Intervention (DS1-EI)". In DS1-EI, trained teachers worked one-to-one with each child in a small classroom setting, offering 10 h per week of the intervention. The focus was on encouraging spontaneous communication, promoting skills through play with peers, supporting positive interactions, and developmental and sequenced learning. We enrolled 5- to 9-year-old children with ASD and ID across 11 French child care institutions for children with co-occurring ASD and ID. Participants were matched in dyads by developmental quotient and randomized to the treatment-as-usual (TAU) group or the DS1-EI group. Independent raters blindly assessed the primary variables: The Childhood Autism Rating scale (CARS) and the Psychoeducational Profile, third edition (PEP-3). The secondary variables included the Vineland Adaptive Behavior Scale II (VABS-II) and the Clinical Global Assessment Scale (CGAS). Here we perform interim analyses at 24 months. Results At baseline, 72 participants were randomized. Nine patients (5 in the DS1-EI group and 4 in the TAU group) dropped out of the study. Using linear mixed models, both intent-to-treat (ITT) and per-protocol (PP) analyses at the 12-, 18- and 24-month outcomes showed no significant group nor group-by-time interaction effects. However, we found significant improvements in most primary and secondary variables over time in both groups. Conclusions The study did not show that DS1-EI was superior to TAU in treating children with ASD and ID over 24 months. However, the low dropout rate shows that DS1-EI is feasible, and well accepted. As the study is still ongoing, we need to wait for data at 36 months to ensure whether DS1-EI could be recommended. Trial registration ANSM130282B-31 (April 16, 2013) and ACTRN12616000592448 . Registered 6 May 2016, retrospectively registered, http://www.anzctr.org.au/